Forms of Magnesium in Aeolian and Alluvial Plain Soils of Arid Rajasthan - Choudhari, J S (Annals of Arid Zone, 2016)
Forms and occurrence of magnesium (Mg) in eight pedons on aeolian and alluvial plains of arid Rajasthan were studied. The cont nts of various forms were higher than in the soils of other regions. Quantities (mg/lOO g soil) of different forms of Mg were: water soluble (9 to 40). exchangeable (3 to 38), ammonium acetate soluble (15 to 571. organic bound (0 to 43). reserve (120 to 519). and mineral (81 to 651), respectively representing I to 5, 0.5 to 3, 2 to 5, o to 3, ]7 to 40 and ]6 to 47 per cent of the total (0.597 to 2.648 g/1OO g soil) content. Variations in Mg content were largely due to differences in the parent material. Type and proportion of 2:1 minerals influenced the exchangeable anti reserve forms of Mg whereas mineralogy of fine sand influenced the content of mineral form of Mg. Free CaC03 contained 10 to 30% of the total Mg. Various forms of Mg were significantly inter-related.